Debt capital access procedures for small and medium-sized enterprises in an emerging economy: does financial knowledge matter? - James Tuffour; Albert Acheampong; Enoch Mensah-Williams; John Hector Amonoo (Cogent Business & Management)
Small and Medium-Sized Enterprises (SMEs) play a crucial role in the development of emerging economies. However, access to debt financing poses a major challenge to their sustenance and growth. This quantitative study explored the Perking order and trade-off theories to analyse data from 201 SME operators in Ghana on the effect of debt capital access procedures and financial knowledge. This study contributes to the ongoing discussion on SMEs’ sustainable financing, and may influence policy on financial support to SMEs operating in marginalised sectors of emerging economies. The findings indicate that bureaucratic debt approval processes significantly hinder SMEs’ access to debt finance. Again, we found that SME operators’ financial knowledge does not aid access to debt capital. It is therefore suggested that simplifying credit approval processes and improving SME operators’ financial literacy through training could enhance SMEs’ ability to secure debt finance. This will contribute to the financial inclusion of marginalised groups and bridge the economic inequality gap to promote inclusive and sustainable growth. Additionally, we recommend that government agencies responsible for SMEs provide special funds to augment those provided by the private sector.